Trauma of Maoist insurgency in literature: Reading Palpasa Café, Forget Kathmandu and Chhapamar ko Chhoro - Acharya, Khagendra (Bodhi: An Interdisciplinary Journal, 2013)
Bodhi: An Interdisciplinary Journal, 5, 2011, Page 80-110 DOI: http://dx.doi.org/10.3126/bodhi.v5i1.8046